2013
DOI: 10.1080/14634988.2013.857974
|View full text |Cite
|
Sign up to set email alerts
|

Invasion and impacts of alien fish species in the Ganga River, India

Abstract: In this study, we document an increasing trend of catches of alien fish species from the Ganga River system. The changing fishery during 1980 to 2011 and the fish yield rate (kg km −1 ) are positively correlated with an invasion coefficient index (I xi ) of alien species within the river. The reproductive propagule pressure (PPP) of alien fishes (Cyprinus carpio, Oreochromis niloticus, Aristichthys nobilis, Ctenopharyngodon idella, Hypophthalmichthys molitrix and Clarias gariepinus) was determined and found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 8 publications
2
43
0
Order By: Relevance
“…), C. carpio is either historically recognised as a pest species (USA: Panek ) or being monitored as potentially invasive (India: Singh et al . , ). By contrast, in some European countries (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…), C. carpio is either historically recognised as a pest species (USA: Panek ) or being monitored as potentially invasive (India: Singh et al . , ). By contrast, in some European countries (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies from the Yamuna and Ganga rivers have shown that there is a constant increase in the yield of alien varieties. In Yamuna, the occurrence of tilapia, African catfish, silver carp and Gambusia is higher and the yield is spiralling every year 10,15 . Singh et al 15 reported the highest yield of exotic variety of 384.27 kg/km in the Ganga.…”
mentioning
confidence: 99%
“…In Yamuna, the occurrence of tilapia, African catfish, silver carp and Gambusia is higher and the yield is spiralling every year 10,15 . Singh et al 15 reported the highest yield of exotic variety of 384.27 kg/km in the Ganga. Likewise, studies from Kerala have shown the high occurrence of tilapia species in inland waters (up to 25%), due to which native species such as Puntius dubius and Labeo kontius face local extinction 13 .…”
mentioning
confidence: 99%
See 2 more Smart Citations